2015
DOI: 10.1007/s00464-014-3987-7
|View full text |Cite
|
Sign up to set email alerts
|

Remission of type 2 diabetes after omega loop gastric bypass for morbid obesity

Abstract: OMBP is effective treatment for obesity in terms of weight loss and remission of T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 44 publications
0
6
0
2
Order By: Relevance
“…The efficacy of MGB/OAGB in providing diabetes remission is confirmed in long-term studies as well. Lee reports a significantly lower level of HbA1c at 5 years in patients who underwent MGB/OAGB vs. SG in a RCT [40], while Guenzi reported 82.5 % of diabetes control with HbA1c lower than 6.5 %, after a mean follow-up of 26 months, following MGB/ OAGB [41]. This is also confirmed in our Italian multicenter experience, reporting a T2DM remission rate of 84.4 % at 5 years of follow-up [42].…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of MGB/OAGB in providing diabetes remission is confirmed in long-term studies as well. Lee reports a significantly lower level of HbA1c at 5 years in patients who underwent MGB/OAGB vs. SG in a RCT [40], while Guenzi reported 82.5 % of diabetes control with HbA1c lower than 6.5 %, after a mean follow-up of 26 months, following MGB/ OAGB [41]. This is also confirmed in our Italian multicenter experience, reporting a T2DM remission rate of 84.4 % at 5 years of follow-up [42].…”
Section: Discussionmentioning
confidence: 97%
“…2 studies did not report their mortality rate. [21,26] In the remaining studies, mortality rate ranged 0.08%-0.9%. Not including the 2 studies where mortality was not reported, overall mortality rate was 0.152%.…”
Section: Efficacy-weight Loss and Resolution Of T2dmmentioning
confidence: 98%
“…T2DM remission rates were mostly more than 84% [18,[20][21][22][23][26][27][28][29] Table 2 details the summary of complications in the same studies. 9 studies reported 0% mortality in their series.…”
Section: Efficacy-weight Loss and Resolution Of T2dmmentioning
confidence: 99%
“…Les bypass consistent en une réduction de la taille de l'estomac associée à un court-circuitage d'une partie de l'intestin grêle. Ce court-circuit a d'abord été réalisé « en Y », technique évaluée et recommandée par la Haute Autorité de santé 3 , puis une autre technique -dite « en oméga » -s'est largement diffusée.…”
Section: Communiqué De Presse De La Has : La Has Est Défavorable Au Runclassified
“…J'ai commencé à étudier l'OAGB en 2006, après la première étude randomisée de WJ Lee. Je me suis astreint à étudier cette opération de la façon la plus académique en publiant toutes les complications parmi les 1 000 premiers patients [1], les résultats fonctionnels à 5 ans [2] et les rémissions des 100 premiers diabètes opérés [3]. Connaissant la controverse autour des risques potentiels de l'OAGB, j'avais spécifié que s'il y avait la moindre raison de récuser cette opération je l'écrirais.…”
Section: La Conclusion En a éTé : La Has Considère Que Le Bypass Gastunclassified